1999
DOI: 10.1109/52.795103
|View full text |Cite
|
Sign up to set email alerts
|

Architectures, coordination, and distance: Conway's law and beyond

Abstract: Software engineering researchers have long argued that the architecture of a system plays a pivotal role in coordinating development work. Over 30 years ago, Melvin Conway proposed what has since become known as Conway's Law-that the structure of the system mirrors the structure of the organization that designed it. 1 This relation, Conway argued, is a necessary consequence of the communication needs of the people doing the work. David Parnas, in fact, defined a software module as "a responsibility assignment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
264
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 284 publications
(276 citation statements)
references
References 7 publications
11
264
0
1
Order By: Relevance
“…Therefore, virtual teams rely on trust; but it takes time to establish trust in complex environments [32,43,50] like in a FOSS ecosystem. Building trust is important for team coordination, as it has been reported that the lack of trust is a barrier to team coordination that geographically distributed organizations face [28,29].…”
Section: Lesson 1: Ensure That the Release Team Follows The Main Commmentioning
confidence: 99%
“…Therefore, virtual teams rely on trust; but it takes time to establish trust in complex environments [32,43,50] like in a FOSS ecosystem. Building trust is important for team coordination, as it has been reported that the lack of trust is a barrier to team coordination that geographically distributed organizations face [28,29].…”
Section: Lesson 1: Ensure That the Release Team Follows The Main Commmentioning
confidence: 99%
“…Adopting an architecture tends to guide developers toward compatible decisions, assuming there is effective communication and a common understanding of what the architecture actually is [37,54].…”
Section: Software Architecturementioning
confidence: 99%
“…Locational asynchrony arises from factors like differences in geography and time zones. An example of LA would be the difficulty in explaining a simple architectural block diagram over email or telephone conversation, which can be easily accomplished with a white board and markers in a room of people (something similar to the consequence of distance highlighted in [10]). Perceptional asynchrony tends to be more subtle, and is caused by the complex interplay of stakeholder interests that dispersed development essentially entails.…”
Section: Interpretation Of the Resultsmentioning
confidence: 99%
“…Herbsleb and Grinter in their papers [10], [11] have taken a more social view of distributed software development. In terms of Conway's Law -organizations which design systems are constrained to produce designs which are copies of the communication structures of these organizations [4] -Herbsleb and Grinter seek to establish the importance of the match between how software components collaborate and how the members of the teams that develop the software components collaborate.…”
Section: Related Workmentioning
confidence: 99%